RESEARCH REGARDING THE IDENTIFICATION OF THE FUNGUS PHOMOPSIS MALI ROBERTS (PHOMOPSIS FRUIT TREE CANKER) IN A TWO YEARS OLD ECOLOGICAL APPLE ORCHARD - CASE STUDY - Otilia COTUNA; Mirela PARASCHIVU; Veronica SĂRĂȚEANU; Marinel Nicolae HORABLAGA; Andi CIOBANU; Klaudia KINCEL; Anca Ofelia PANDA; Ramona ȘTEF (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Phomopsis mali Roberts (Phomopsis fruit tree canker) is a fungus that infects the fruit tree trunks, branches and sprigs. There were described more than 60 species of Phomopsis. Every of the species is identified in general after the size of the conidia and after the host from which was isolated, the precise identification being sometimes difficult. Phomopsis is a fungus that can produce serious damages in production because it affects the fruitful sprigs. On the other hand, in case of massive attacks it can lead to the fruit trees decline. In the young orchards cultivated in ecologic super-intensive system, the young trees can die in the case of severe infections. The purpose of this research was to identify the Phomopsis fungus in an ecologic super-intensive apple orchard from Arad County (western Romania), in the first two years after the plantation. The biological material used was consisting in six samples sets (sprigs, stems, branches and roots) collected from four apple varieties (Primiera/M9, Crimson Crisp/M9, Golden Orange/M9 and GoldRush/M9). The identification of the disease and of the pathogen was done using visual and laboratory methods. In laboratory was identified the fungus with the humid chamber method and by placement of diseased tissue samples on culture medium followed by incubation at 23 - 24oC for seven days. The branches, sprigs and stems were analysed at stereomicroscope too. Under the cracked bark were identified numerous pycnidia of black colour and pear shaped, specific to the Phomopsis mali fungus. There were noticed young and old fructifications, the old ones were from the previous year or even from the precedent years. The obtained results after the visual analysis of the trees in the orchard and after the laboratory analyses highlighted the presence of the fungus Phomopsis mali. There were highlighted at the microscope the alpha and beta conidia, typical for this fungus. In the orchard all the trees were presenting symptoms specific to the Phomopsis fruit tree canker. The trees covered with numerous canker lesions were died. At the assessment time the dead trees rate on varieties was the following: Primiera – 16.5%, Crimson Crisp – 1.7%, Golden Orange – 16.1%, and Gold Rush – 17.2%. From all the analysed apple varieties only Crimson Crisp had reacted well to the attack of the Phomopsis mali fungus.